Zimbabwe : 2000 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; Statement by the Executive Director for Zimbabwe and Statement by the Authorities of Zimbabwe. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Fiscal profligacy, an erosion of competitiveness, and governance problems have undermined investor confidence and curtailed access to foreign financing in Zimbabwe. The new economic team has taken steps in devaluing the currency and raising the awareness of public opinion about the size of the fiscal deficit and its root causes. Steadfast implementation of strong policies, backed by a broad domestic consensus, will help restore Zimbabwe's status as an anchor of stability and prosperity in southern Africa over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet